Retraction Note Retracted Article: Prevalence of Incidental Amblyopia in Buraidah City - Vishakh Nair, Manzoor Ahmed Qureshi, Mohammad Ijaz Ahmed, Yousef Hamood Al-debasi (Pakistan Journal of Ophthalmology, 2018)
Received: 30 May 2012 / Accepted: 04 November 2012 Pak J Ophthalmol 2012, Vol. 28, No. 3 RETRACTION STATEMENT The article has been retracted by agreement between the authors and the editors. The reasons for retraction are twofold: First author Mr. Manzoor Ahmed Qureshi failed to get permission from the Qassim University, Kingdom of Saudi Arabia to publish the data which was supervised and analysed by Dr. Yousaf Aldebasi. The head of Optometry Department, Qassim University, Kingdom of Saudi Arabia asked Mr. Manzoor Qureshi to retract the article as he was the first author. All listed authors agree on the fact that the article should be retracted due to contention of authorship. Therefore this publication should be ignored. Dr. Manzoor apologizes to all authors and to the editors and readership of the Pakistan Journal of Ophthalmology.